Analisis Strategi Badan Pelaksana Otorita Danau Toba Dalam Mengembangkan Pariwisata Danau Toba - Ahmad Zikri; Nurbaiti Nurbaiti; Nurwani Nurwani (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to first determine and analyze the Lake Toba Tourism development strategy by the Lake Toba Authority Implementing Body. Second, to find out the results of the SWOT analysis of employee performance improvement strategies using the IFAS and EFAS matrices, important factors can be identified from both the external environment and the internal environment which are strengths, weaknesses, opportunities and threats for improving performance. The research method used in this research is descriptive qualitative, the author also uses SWOT analysis. SWOT analysis is the systematic identification of various factors to formulate company strategy. From the results of the analysis, a growth strategy or growth oriented strategy is obtained. This strategy indicates that the company is strong and able to continue to develop by taking advantage of existing opportunities. This strategy was chosen because the calculation results were in quadrant I where the total weighted score of strengths-weaknesses was 3.36 while the total weighted score of opportunities-threats was 3.314. Positions in this quadrant are very profitable and can be implemented optimally.